2017
DOI: 10.1136/heartjnl-2016-310216
|View full text |Cite
|
Sign up to set email alerts
|

Gender inequalities in cardiovascular risk factor assessment and management in primary healthcare

Abstract: 12611000478910, Pre-results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
99
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 14 publications
8
99
1
3
Order By: Relevance
“…We observed effects on age, sex, race, and comorbidity that we controlled for in the assessment of effects on health outcomes. Female patients had a slightly greater risk of death than men that may be related to less attention to cardiovascular risk factors and lower prescribing of effective medications in women than in men . The effects of race on mortality and utilization outcomes could be the result of variation in cardiovascular medication prescribing to racial and ethnic minorities and their adherence to treatments …”
Section: Discussionmentioning
confidence: 99%
“…We observed effects on age, sex, race, and comorbidity that we controlled for in the assessment of effects on health outcomes. Female patients had a slightly greater risk of death than men that may be related to less attention to cardiovascular risk factors and lower prescribing of effective medications in women than in men . The effects of race on mortality and utilization outcomes could be the result of variation in cardiovascular medication prescribing to racial and ethnic minorities and their adherence to treatments …”
Section: Discussionmentioning
confidence: 99%
“…70 Gender disparities in CVD prevention are age dependent, as shown by an analysis of the Treatment of cardiovascular Risk in Primary care using Electronic Decision suppOrt (TORPEDO) study. 71 Women attending primary healthcare services in Australia were less likely than men to have risk factors measured and recorded such that absolute CVD risk can be assessed. For those with, or at high risk of, CVD, the prescription of appropriate preventive medications was more frequent in older women but less frequent in younger women, compared with their male counterparts.…”
Section: Other Relevant Groupsmentioning
confidence: 99%
“…Women are less likely than men to have their cardiac risks assessed, with the majority not adhering to appropriate primary prevention guidelines and instead resorting to nonevidence-based therapies. 45,46,79 Similarly, EUROASPIRE III and IV surveys demonstrated that despite the higher burden of comorbidities at time of presentation of MI, women are less likely to receive recommended pharmacotherapies (Figure 4) 47,48 and less likely to achieve secondary prevention targets for hyperlipidemia (OR, 0.5), hyperglycemia (OR 0.78), physical activity (OR, 0.74), or body mass index (OR, 0.82). 47,51,52 These disparities are most prominent in Black women, the majority of whom have ≥3 traditional risk factors and yet are significantly less likely to receive appropriate secondary prevention compared with age-matched White women after hospitalization for MI.…”
Section: Less Intense Pharmacotherapymentioning
confidence: 99%